2007
DOI: 10.4018/jswis.2007040101
|View full text |Cite
|
Sign up to set email alerts
|

Experience in Aligning AnatomicalOntologies

Abstract: An ontology is a formal representation of a domain modeling the entities in the domain and their relations. When a domain is represented by multiple ontologies, there is need for creating mappings among these ontologies in order to facilitate the integration of data annotated with these ontologies and reasoning across ontologies. The objective of this paper is to recapitulate our experience in aligning large anatomical ontologies and to reflect on some of the issues and challenges encountered along the way. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 27 publications
0
39
0
Order By: Relevance
“…As most tools are still highly experimental and not used in practical applications, the fi rst evaluation efforts favored mostly "application-independent" methods. 3 Researchers typically created and used manually built reference alignments (or gold standards) that were often biased toward-at best-one single usage scenario (for example, vocabulary merging), with little use for other scenarios. More recent evaluation approaches have adopted more realistic assessments by using, for instance, application-specifi c sampling methods and measures.…”
Section: Discussionmentioning
confidence: 99%
“…As most tools are still highly experimental and not used in practical applications, the fi rst evaluation efforts favored mostly "application-independent" methods. 3 Researchers typically created and used manually built reference alignments (or gold standards) that were often biased toward-at best-one single usage scenario (for example, vocabulary merging), with little use for other scenarios. More recent evaluation approaches have adopted more realistic assessments by using, for instance, application-specifi c sampling methods and measures.…”
Section: Discussionmentioning
confidence: 99%
“…Work on ontology mapping related with rules can be found in [11] where mapping heuristics were stated as rules and in [12] where manually established mappings were represented as rules in order to support agent communication. In one of our previous studies [13], we used Jena rules to identify the granularity differences in ISA classification between ontologies, of which the work in this paper is a direct follow-up.…”
Section: Introductionmentioning
confidence: 99%
“…State-of-the art match systems such as COMA++ [2], Falcon [16] or SAMBO [21] combine multiple matchers within a match strategy to achieve better match quality. Results of matching biomedical ontologies showed that linguistic matching methods based on the similarity of concept names and synonyms produce very good results [35,12]. To improve the runtime of matching (especially for large ontologies) some systems try to reduce the search space [17] or perform parallel matching on multiple compute nodes [13].…”
Section: Related Workmentioning
confidence: 99%